Assessment of biological activities of chitosan Schiff base tagged with medicinal plants. Issue 3 (7th November 2019) - Khan, Arshad Mehmood; Abid, Obaid ur Rehman; Mir, Sadullah
Abstract: A chitosan Schiff base with an aromatic aldehyde was synthesized and characterized by FTIR and NMR spectroscopies. Furthermore, the degree of substitution was calculated based on the ratios of the area of the proton of the imine ( A imine ) and the area of the peak of the proton of the pyranose ring ( A H‐2 ). The antimicrobial activities were determined against bacterial and fungal strains, as well as multiple drug‐resistant (MDR) bacteria. The chitosan Schiff base was also tagged with medicinal plants, for example, Curcuma longa, Peganum harmala, Lepidium sativam, and cruciferous vegetables, and the biological activities determined against pathogenic bacterial and fungal strains. The chitosan Schiff base showed maximum zone of inhibition of 22 mm against Staphylococcus aureus with a minimum zone of inhibition of 15 mm against Bacillus cereus . The chitosan Schiff base was fused with C longa, isothiocyanates and a combined mixture of P harmala and L sativam that has shown activities against Escherichia coli with a zone of inhibition of 28, 24, and 30 mm, respectively. The Schiff base of chitosan fused with medicinal plants also showed significant inhibitory activities against MDR bacteria. Abstract :